CO2 capture with the absorbent of a mixed ionic liquid and amine solution considering the effects of SO2 and O2. (15th May 2017) - Yang, Jie; Yu, Xinhai; An, Lin; Tu, Shan-Tung; Yan, Jinyue
Graphical abstract: Highlights: The addition of IL to MEA aqueous solution reduced the losses of MEA and water. O2 and SO2 played less important roles in the losses of MEA and water than evaporation. The thermal energy at stripper of IL mixed absorbent is 33.8% lower than that of aqueous MEA solution. Abstract: Room-temperature ionic liquids (ILs) have recently been proposed as a potential candidate for CO2 capture. In this study, experiments were conducted in an absorption-desorption loop system to investigate the effects of SO2 and O2 on CO2 capture using an aqueous amine solution mixed with IL. The gas mixture containing CO2, O2, SO2 and N2 in the composition range of flue gas from a coal-fired power plant after flue gas desulfurization was selected as the feed gas. It was found that the addition of hydrophilic IL of 1-butyl-3-methylimidazolium tetrafluoroborate ([bmim][BF4 ]) to a monoethanolamine (MEA) aqueous solution reduced the losses of MEA and water by lowering the saturated vapour pressure of the mixed absorbent. For hydrophobic IL of 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide ([hmim][Tf2 N]), the MEA loss for 30 wt% MEA + 70 wt% [hmim][Tf2 N] increased dramatically with the system running because carbonate, which was formed by MEA reacting with CO2, was insoluble in [hmim][Tf2 N] at the absorber operation temperature of 323 K. The effects of O2 and SO2 were relatively insignificant for the MEA and water losses. The aqueous amine solution mixed with [bmim][BF4 ] showed good performances with a CO2 removal efficiency of above 90% and the SO2 concentration at the absorber outlet below 20 ppb. No obvious IL loss was detected. For the absorbent of 30 wt% MEA + 50 wt% [bmim][BF4 ] + 20 wt% H2 O, the thermal energy consumption for absorbent regeneration is 33.8% lower than that of the aqueous MEA solution.